2004
DOI: 10.1523/jneurosci.0154-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Calcium–Calmodulin-Dependent Kinase II Modulates Kv4.2 Channel Expression and Upregulates Neuronal A-Type Potassium Currents

Abstract: Calcium-calmodulin-dependent kinase II (CaMKII) has a long history of involvement in synaptic plasticity, yet little focus has been given to potassium channels as CaMKII targets despite their importance in repolarizing EPSPs and action potentials and regulating neuronal membrane excitability. We now show that Kv4.2 acts as a substrate for CaMKII in vitro and have identified CaMKII phosphorylation sites as Ser438 and Ser459. To test whether CaMKII phosphorylation of Kv4.2 affects channel biophysics, we expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
132
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(153 citation statements)
references
References 56 publications
18
132
3
Order By: Relevance
“…In dendrites I Ar attenuates backpropagating APs. Numerous studies have shown that during depolarizing current injections the shunting inhibition provided by I Ar increases rheobase, delays the onset of AP discharge, and increases interspike interval (Mitterdorfer and Bean 2002;Molineux et al 2005;Russier et al 2003;Varga et al 2004;Vydyanathan et al 2005). Our data suggest an additional role for I Ar , where the shunting inhibition actually prevents AP discharge in reluctant firing neurons altogether.…”
Section: Ap Discharge Propertiessupporting
confidence: 50%
“…In dendrites I Ar attenuates backpropagating APs. Numerous studies have shown that during depolarizing current injections the shunting inhibition provided by I Ar increases rheobase, delays the onset of AP discharge, and increases interspike interval (Mitterdorfer and Bean 2002;Molineux et al 2005;Russier et al 2003;Varga et al 2004;Vydyanathan et al 2005). Our data suggest an additional role for I Ar , where the shunting inhibition actually prevents AP discharge in reluctant firing neurons altogether.…”
Section: Ap Discharge Propertiessupporting
confidence: 50%
“…The amplitude of the second transient represents the amount of whole-cell A-type current that is mediated by Kv4 channels. The difference between the first transient and the second transient represents the amount of Kv1-mediated current that would not be expected to recover from inactivation during the 100 ms hyperpolarization (Varga et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Setting our search parameters at the highest level of stringency produced the list of 12 kinases shown in Table 1. Of this list, three kinases had previously described actions on voltage-gated ion channels: protein kinase C (PKC), calcium/calmodulin-dependent protein kinase II (CAMKII), and p38 MAPK (Varga et al, 2004;Chen et al, 2005;Wittmack et al, 2005). Of the entire list, p38 MAPK had the highest score for likely HCN interactions, and was predicted to phosphorylate both HCN1 and HCN2.…”
Section: Resultsmentioning
confidence: 99%